(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: A study to assess the current situation of antibiotic use in surgery and its influencing factors at the Department of Surgery, Tra Vinh Provincial General Hospital. The results: The overall rate of patients using antibiotics was 44, 78%, and on surgery was 100%. Several factors affect antibiotic use: age, gender, and use of medical insurance. In addition, the study identified some factors that determine the use of antibiotics: Treatment regimens, decision to choose antibiotics for patients and doctors, antibiotic supply of the Faculty of Pharmacy, and information on drug updates. Recommendations: Develop regulations on drug use and drug combination; clarify the criteria for drug use, develop quality standards and provide indicators to assess drug resistance. Improve the management of drug use by doctors and clinical departments.